Clinical Nurses' Perceptions of a Senior Capstone Dedicated Educational Unit. Issue 2 (March 2019) - Glynn, Donna M.; Wendt, Judith; Russell, Bonnie; Conley, Grace; Hill, Patrick
Abstract : Abstract: Clinical nurses' perceptions of a senior capstone dedicated educational unit (DEU) model to transition to practice was evaluated in a pilot study. Nursing students were placed in the traditional capstone and the DEU senior capstone unit with clinical nurses. Staff nurses completed an online survey to compare and contrast satisfaction and effectiveness of the models. The results of the study revealed no perceived differences in the outcomes of a DEU experience as compared to the traditional preceptor model. However, nursing management reported an improved sense of leadership and teamwork on the unit with the DEU model.